(untitled) - Lin, Feng (Chichester, West Sussex, England ; Hoboken, NJ, 2007)
Optimal control is a mathematical field that is concerned with control policies that can be deduced using optimization algorithms. The optimal control approach to robust control design differs from conventional direct approaches to robust control that are more commonly discussed by firstly translating the robust control problem into its optimal control counterpart, and then solving the optimal control problem
Keywords: Automatic control,Điều khiển tự động